A PROPOSAL OF THETICAL ECONOMY AND ANTITHETICAL ECONOMY BY USING OPERATIONS RESEARCH TECHNIQUES - Kinoshita, Eizo (European Scientific Journal, ESJ, 2015)
In this paper, the author Kinoshita proposes Thetical and Antithetical economies in macroeconomics by utilizing the technique of operations reserach (OR). The author also states the economy naturally goes through a bubble economic phase, followed by its bursting, when it moves from Thetical Economy to Antithetical Economy. Thus, the author analyzes and identifies how each of the four economic phases (Thetical Economy, bubble economy, the bursting of the bubble, Antithetical Economy) is to be formed. The author also believes that the two major economic events in the past, or the prolonged recession in Japan over the last 20 years, and the global downfall in stock prices triggered by the 2008 U.S. sub-prime loan crisis, which adversely affected general consumers, presented significant difficulties within the study of economics. It is the position of this paper that Japan’s recession and the U.S. sub-prime loan crisis have revealed a new fundamental economis truth, in view of the fact that macroeconomics was born from the Great Depression, a prolonged slump that originated in the United States 80 years ago.